Time Clauses with kuomet in Old and Modern Lithuanian - Pajėdienė, Jūratė (Vilnius University Open Series, 2018)
[full article and abstract in Lithuanian; abstract in English] This article discusses the usage of subordinate clauses of time with kuomet in Old Lithuanian and Modern Lithuanian. The morphosyntactic structure of time clauses with kuomet, recorded in old Lithuanian writings (both translations and original texts), is rather similar: they are usually employed to emphasize the exceptionality of a certain moment or situation; therefore, they use negatives or other syntactic means that highlight exceptionality rather frequently, whereas time clauses with kuomet become an important part of the argumentative discourse. Situational, semantic and positional models of time clauses containing kuomet show that kuomet used in the time clauses of old Lithuanian writings meets all the necessary parameters of an adverbial subordinator. The usage of time clauses with kuomet in the original works of the authors of the old writings attributed to different dialects – Jonas Bretkūnas, Zacharijus Blothnas and Konstantinas Sirvydas – prevents us from considering kuomet as a dialecticism. The time clauses with kuomet used in Modern Lithuanian are also used to describe the situations of two actions that are related to exceptionality and the importance of a special moment. This enables us to define kuomet as a traditionally inherited adverbial subordinator of time clauses and to stop doubting the grammatical and contextual suitability of this subtype of time clauses for Modern Lithuanian.